Suitability of Yushania Alpina for Oriented Particleboard - Haile, Seyoum Kelemwork (2005)
Highland bamboo (Yushania alpina) and lowland bamboo (Oxytenanthera abyssinica) are widespread in Ethiopian. Both covering approximately 1 million hectare of land. No commercial importance has been found for these lignocellulose materials. It is thus the main objective of this study is to determine the suitability of Yushania alpina for the manufacture of oriented particleboard. Yushania alpina from three major bamboo growing areas, namely Ambo, Bore and Masha of three age groups of bamboo (one, two and three year-old) were used for this study. The effects of bamboo growing sites and age variation on mensurational attributes (i.e., culm basal diameter, culm wall thickness, culm volume and weight) and on basic properties (i.e., moisture content, density, anatomical characteristics, buffering capacity and wettability of bamboo) were statistically analyzed using completely randomized design. The analysis indicated that mensurational attributes and basic properties of vary with respect to growing sites, ages and culm height. Homogenous, three-layered oriented from fine particle sizes, three-layer oriented from coarse particle sizes and three-layered oriented conventional (a mixture of fine and coarse particles) bamboo particleboards were manufactured using 10% ureaformaldehyde resin to evaluate the effects of particleboard processing parameters such as board density, particle size, particle orientation and particle layering on mechanical properties and dimensional stability. The completely randomized design with factorial experiments was used in the analysis. The results show that the mechanical properties and dimensional stability of homogenous boards made from three-year old bamboo varied among the growing sites. Age of bamboo did not show significant effects on strength and stiffness properties of homogenous bamboo particleboards. It was also found that the internal bond strength of bamboo particleboards decreased as the bamboo gets older whilst thickness swelling increased. The modulus of rupture (MOR) and modulus of elasticity (MOE) of three-layered oriented bamboo particleboards produced from fine particle sizes and three-layered oriented bamboo particleboards produced from coarse particles were significantly affected by particle alignment and sizes. Both types of particleboards made from fine and coarse particle sizes and parallelly aligned to the longitudinal axis of the boards had superior strength (about 15%) compared to random oriented boards. Similar comparisons of the MOE between oriented and random boards showed that MOE of parallelly aligned boards to the longitudinal axis of the boards was higher by 28% and 37%, respectively for both fine and coarse particle size oriented boards than those of random boards. The internal bond strength, thickness swelling and water absorption of oriented bamboo particleboards showed insignificant variation with particle alignment. However, boards made from fine particle sizes gave 35% higher IB strength and 12% dimensionally stable oriented boards than those made from coarse particle. The screw withdrawal resistances of oriented bamboo particleboards were affected by particle alignment and particle size. Boards made from coarse particles that were randomly oriented particles had superior screw withdrawal resistance than that made from fine particles. The properties of three-layered conventional oriented bamboo particleboards were affected by the density profile of the boards. As fine particles at face layer was increased from 20% to 30% (based on the weight of the board) the MOR and MOE of the boards increased from 27 MPa to 41 MPa and 4.9 GPa to 6.1 GPa, respectively. The thickness swelling (TS) decreased from 7.5 to 5.8 % and the internal bond (IB) strength increased from 0.60 MPa to 0.69 MPa. The presence of high amount of fine particle at the face layers and high internal bond strength increased significantly screw withdrawal resistance. In general, vertical density profile has significant impact on strength and stiffness properties of three-layered boards. Three-layered boards that have steeper density gradient (higher average face layer density and low core density) have high strength and stiffness properties than three-layered boards which have relatively more uniform density profile. Regression equations of three-layered boards relating the proportion of fine particles on the face layer to coarse particles in the core layer may be used to predict the MOR, MOE, IB strength and TS of three-layered particleboards produced in this study. Generally, the strength and dimensional stability of particleboards manufactured from Yushania alpina bamboo met the ISO standards ISO/DIS 16978, ISO/DIS 16984 and ISO/DIS 16983 for high performance general purpose particleboards